Inert hydrophilic particles enhance the thermal properties and structural resilience of meat protein gels during heating. Issue 2 (7th January 2021) - Katz, Felix-Alexander; Grossmann, Lutz; Gerhards, Christian; Weiss, Jochen
Abstract : Meat protein gels are present in a variety of foods and are frequently filled with fat particles. Abstract : Meat protein gels are present in a variety of foods and are frequently filled with fat particles. This study set out to elucidate the effect of replacing hydrophobic fat-based particles with hydrophilic inert glass particles on thermal and structural properties during heating. Meat protein gels were prepared with different diameters (60 to 90 mm) according to a typical emulsified sausage recipe and fat-based particles as well as inert glass particles were incorporated at concentrations from 10 to 40% and heated to 85 °C, while thermal as well as structural properties were monitored. The results revealed two main effects. First, due to the higher thermal conductivity, the lower heat capacity and the absence of extensive phase transitions, the time to reach the final temperature was reduced with increasing glass particle content ( e.g. from 118 ± 2 min with 40% fat particles to 86 ± 1 min for gels with 40% glass particles at a depth of 40 mm). Second, volume change and temperature sweep measurements revealed that glass particles fostered the protein gel formation and enhanced the resilience against structural breakdown during heating. This was evident during small-amplitude shear experiments that showed an almost twofold increase in the storage modulus when 10% fat-based particles were replaced with 10% glass particles from G ′85 °C = 223.4 ± 14.8 kPa to G ′85 °C = 431.0 ± 16.6 kPa, respectively. Overall, these findings might be of interest to meat-product manufacturers that seek to lower heating times to reach the core temperature necessary for protein denaturation and ensure microbial safety with additional holding times and modify the structural properties of foods while replacing fat particles.